Utilizing of crumb rubber derived recycled scrap tires in masonry application: A review - Al-Fakih, A. (Trans Tech Publications Ltd, 2021)
The disposal of scrap tires has resulted in major environmental problems worldwide. Therefore, utilizing scrap tires as Crumb rubber is being used in brick production to improve the properties of the bricks as well as to provide feasible waste management of scrap tires. This study presents the literature research on utilizing crumb rubber in bricks manufacturing. The review summarized the manufacturing process of producing crumb rubber and then documented the application of crumb rubber in masonry. The results show that the compressive strength of masonry bricks decreases with the increased percentage substitution of crumb rubber as a replacement of fine aggregate while the water absorption increased. Moreover, the addition of crumb rubber in masonry applications reduce the density which produce lightweight masonry products. Generally, the findings confirmed that the masonry bricks incorporated crumb rubber exhibit good physical and mechanical properties. The usage of crumb rubber in bricks making helps to solve problems associated with scrap tire management all over the world. Â© 2021 Trans Tech Publications Ltd, Switzerland.